Ladrang Siyem: The Royal Anthem of Thailand, in Javanese Gamelan Version - Jamnongsarn, Surasak; Detkrut, Phunchita; Wangsaptawee, Yotin (Institut Seni Indonesia Yogyakarta, 2023)
Ladrang Siyem: The Royal Anthem of Thailand, in Javanese Gamelan Version. During 19th century, Thailand modernized by associating itself with the